Nutritional Composition And Sensory Evaluation Of Green, Oolong And Black Teas Of Sacha Inchi Leaves - Zarinah Zakaria; Nur Nabilah Norsham; Nur Hasyimah Mat Shah; Nurul Zaizuliana Rois Anwar; Napisah Hussin; Fauziah Tufail Ahmad; Faridah Yahya; Norshazila Shahidan (ResearchersLinks, 2025)
Indexed by Scopus